Analisis Tingkat Stres dan Kualitas Tidur Pada Mahasiswa Universitas Sebelas Maret - Ismail, Khoirudin (Edu Masda Journal, 2023)
The stress level for each student varies from mild stress, moderate stress, and severe stress. This study aims to identify the relationship between stress and sleep quality in students of Building D, FKIP, Sebelas Maret University. This study used an analytic observation method using a quantitative approach and a cross sectional design. The population in this research sample were all students in Building D, FKIP, Sebelas Maret University. The sample in this research was 30 people who were taken using a sampling technique, namely simple random sampling. Data collection use a questionnaire and documentation using chi square data analysis. Based on the results of the research, it was shown that the majority of respondents were Chemistry Education students and were in the 2022 class year. Based on the results of univariate analysis of the stress variable, it was found that the majority of respondents experienced moderate stress, namely as many as 12 respondents with a percentage of 40%. Meanwhile, the results of the univariate analysis of sleep quality revealed that the majority of the respondents had fairly good sleep quality based on aspects of subjective sleep quality, sleep latency, sleep disturbances, use of sleeping pills and activity disturbances, namely 16respondents with a percentage 53,3%. Based on the bivariate analysis using the chi square test, it was found that were was no significant relationship between stress levels and students’ sleep quality, which was indicated by P-valueof 0,1.AbstrakTingkat stres pada setiap mahasiswa berbeda-beda dari stres ringan, stres sedang, dan stres berat. Penelitian ini bertujuan untuk mengidentifikasi hubungan tingkat stres dengan kualitas tidur pada mahasiswa Gedung D, FKIP, Universitas Sebelas Maret. Penelitian ini menggunakan metode observasi analitik dengan menggunakan pendekatan kuantitatif serta desain cross sectional. Populasi dalam sampel penelitian ini sejumlah 30 orang yang diambil menggunakan teknik sampling yaitu simple random sampling. Pengumpulan data menggunkan kuisioner atau angket dan dokumentasi dengan analisis data chi square. Berdasarkan hasil penelitian menunjukkan bahwa sebagian besar responden adalah mahasiswa Pendidikan Kimia dan berada pada tahun angkatan 2022. Berdasarkan hasil analisis univariat terhadap variabel stres diketahui bahwa sebagian besar responden mengalami stres sedang yaitu sebanyak 12 responden dengan persentase 40%. Sedangkan hasil analisis univariat terhadap kualaitas tidur diketahui bahwa sebagian besar responden memiliki kualitas tidur  yang cukup baik berdasarkan aspek kualitas tidur subyektif, latensi tidur, gangguan tidur, penggunaan obat tidur, dan gangguan berakrivitas yaitu sebanyak 16 responden dengan persentase 53,3%. Berdasarkan analisis bivariat dengan uji chi square diketahui bhawa terdapat hubungan yang tidak signifikan antara tingkat stres dan kualitas tidur mahasiswa yang ditandai dengan P-value sebesar 0,1.